1993
DOI: 10.1177/00220345930720090801
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo Study of the Influence of the Surface Roughness of Implants on the Microbiology of Supra- and Subgingival Plaque

Abstract: In nine patients with fixed prostheses supported by endosseous titanium implants, 2 titanium abutments (transmucosal part of the implant) were replaced by either an unused standard abutment or a roughened titanium abutment. After 3 months of habitual oral hygiene, plaque samples were taken for differential phase-contrast microscopy, DNA probe analysis, and culturing. Supragingivally, rough abutments harbored significantly fewer coccoid micro-organisms (64 vs. 81%), which is indicative of a more mature plaque. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
281
1
19

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(318 citation statements)
references
References 25 publications
17
281
1
19
Order By: Relevance
“…Interestingly, NT also reduced the microbial colonies ( Figure 3) to some extent. Rough or textured dental implant surfaces have been shown to enhance bacterial and fungal colonization, 19,20 but the finding of the current study is consistent with the work of Sabrina et al, 18 who found that nanorough Ti decreased the adherence of Staphylococcal aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa. 20 It is believed that the increased surface energy of a nanorough surface leads to greater protein adsorption, 21 and results in decreased bacterial attachment.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, NT also reduced the microbial colonies ( Figure 3) to some extent. Rough or textured dental implant surfaces have been shown to enhance bacterial and fungal colonization, 19,20 but the finding of the current study is consistent with the work of Sabrina et al, 18 who found that nanorough Ti decreased the adherence of Staphylococcal aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa. 20 It is believed that the increased surface energy of a nanorough surface leads to greater protein adsorption, 21 and results in decreased bacterial attachment.…”
Section: Discussionsupporting
confidence: 91%
“…It is known, that chemically etching of glass with nitric acid increases its roughness [51]. Since one of the main criteria for microbial adhesion to glass is the surface roughness, we suggest the etched glass is more susceptible for biofilm formation [52,53]. Even though a prolonged incubation time would lead to a further build-up of biofilm, we found 24 h to be long enough to detect the inhibitory biofilm maturation with the greatest sensitivity (Supplementary Figure S5) [54].…”
Section: Discussionmentioning
confidence: 73%
“…In detail, the pro-cess of acid etching purifies an implant surface through removal of titanium external layers and with them of most of carbonium remnants which are left as sediment after titanium turning. A paper by Morra et al [2] showed a high percentage of carbonium present on the machined surface of a smooth fixture-66% compared to a fixture which is processed with a double acid etching; in this case they recorded a lower percentage of Ca-42,2% The implant Nanotite (Biomet 3i) shows a further reduction of the percentage of superficial carbonium (35,1%) [3]. It is made of a titanium alloy Ti6Al4V and consequently on its surface there is a high content of Alluminum (0,6%), Calcium and P due to the release of nanocrystals of Calcium Phosfate on the surface, which is a peculiar feature of this implant.…”
Section: Discussionmentioning
confidence: 99%